Pathological and Clinical Pathological Studies on Some Immune Stimulant Drugs in Albino Rats - Abou El-Fetouh, Moustafa S.; Elseddawy, Nora M.; Abdelsamia, Hagar M. (Journal of Advanced Veterinary Research, 2023)
A natural fermentation product called ivermectin (IVM), which is generated from the soil bacterium Streptomyces avermitilis, is a broad range of anthelmintic, pesticide, and antiviral. Several immune system functions are impacted by zinc. The goal of the current investigation was to determine how therapeutic doses of ivermectin and monozinc affected the liver, spleen, and lung in terms of histopathological changes, as well as the clinical results of lymphocytes, TNF, and Î³ globulin. Fifteen female white albino rats were equally divided into three groups, group 1 was assigned as a control, and group 2 received a therapeutic dose of ivermectin (0.2 mg/kg BW/SC) with 18 mg of zinc per day orally for one month, and group 3 that received a double therapeutic dose of zinc (0.36 mg/kg BW/SC) orally for one month. The observed macroscopic histopathological changes in group 2 were enlargement of the livers with microscopical mild vacuolation of some hepatocytes with hyperplasia of Kupffer cells. Some areas of the liver showed necrotic changes. The lungs were congested and showed catarrhal pneumonia. The spleens were enlarged and congested, and showed microscopically, hyalinization of the central arterioles with an increase in the lymphocytes of the white pulp and hemorrhage in the red pulp. The histopathological changes in group 3 indicated congestion of the central vein and hepatic sinusoids with hemosiderin pigment and perivascular aggregation of mononuclear cells in the liver, while the lungs, microscopically showed mild catarrhal bronchitis, and the spleen showed hyperplasia of the lymphoid follicle of the white pulp ad reduction of the red pulp. The obtained results of the present study indicated that ivermectin with zinc act as immunostimulants for different cells responsible for immunity in the body tissue. Â 